Co-feeding of pacu, Piaractus mesopotamicus Holmberg (1887), larvae with Artemia naupili and a microencapsulated diet - Tesser, Marcelo Borges [UNESP]; Carneiro, Dalton José [UNESP]; Portella, Maria Célia [UNESP] (Taylor & Francis, 2005)
Aiming at a precocious substitution of live prey by artificial diet, a 20-day experiment with pacu, Piaractus mesopotamicus, larvae using co-feeding and abrupt weaning strategies was set up. At the end of the experiment, larvae fed Artemia showed the best results (P < 0.05) in weight, total length and biomass, compared with other treatments. Larvae fed exclusively a microencapsulated diet never ingested the diet. Diet ingestion in co-fed and abrupt-weaned larvae was low, but did increase during the experiment; however, Artemia influenced diet ingestion on co-fed larvae. Careful considerations should be given to diet processing and formulation to ensure survival and growth of larvae fed exclusively on prepared diets. © 2005 by The Haworth Press, Inc. All rights reserved.
Keywords: Co-feeding; Growth; Larvae; Microencapsulated diet; Pacu; Piaractus mesopotamicus; Survival; artificial diet; feeding; growth; survival; Artemia